GLIAL REGULATION OF CIRCADIAN BEHAVIOR - You, Samantha. (2018)
Abstract: Circadian rhythms are ubiquitous throughout nature. The molecular oscillators that generate these rhythms are components of nearly every part of biological life. While neuronal circadian circuitry is well studied, knowledge about the contribution of glial cells is currently limited. Recent studies in Drosophila and rodents have identified astrocytes as particularly important components of circadian rhythms. Manipulations of clock genes, calcium signaling, glutamate signaling, and vesicle secretion in astrocytes resulted in abnormal circadian behavior. While we now know that astrocytes are important for maintaining circadian rhythms, many questions remain about how these cells interact with circadian circuitry. Given that we know astrocytes communicate with neurons to regulate behavior, I focused my studies on identifying the signals used by these cells. My thesis describes two approaches towards identifying glial components important for behavioral rhythmicity. First, I describe a genome-wide microRNA (miRNA)-based screen to identify brain glial cell processes required for circadian behavior. To identify glial miRNAs that regulate circadian rhythmicity, I employed a collection of "miR-sponges" to inhibit miRNA function in a glia-specific manner. My initial screen identified 20 glial miRNAs that regulate circadian behavior. I studied two miRNAs - miR-263b and miR-274 - in detail and found that both function in adult astrocytes to regulate behavior. Astrocyte-specific inhibition of miR-263b or miR-274 in adults acutely impairs circadian locomotor activity rhythms with no apparent effect on glial or clock cell viability. To identify potential RNA targets of miR-263b and miR-274, I screened 35 predicted miRNA targets, employing RNAi directed against each target. I found that glial knockdown of two putative miR-274 targets - CG4328 and MESK2 - resulted in significantly decreased rhythmicity. Homology of the miR-274 targets to mammalian counterparts suggests mechanisms that might be relevant for the glial regulation of rhythmicity. A second approach to understanding glial functions utilized cell type-specific profiling of fly astrocytes to identify RNAs showing circadian changes in abundance. I used a tagged ribosomal subunit to affinity purify RNA collected from astrocytes across two days for RNA-sequencing. Dr. Amy Yu performed the initial processing of the sequencing data. I then performed qualitative analysis of the results. 724 RNAs were found to exhibit circadian changes in abundance. Of those cycling genes, 576 were determined to be high-confidence astrocyte genes. I confirmed the list included cycling of core clock genes and known astrocyte genes. I performed gene ontology analysis to identify overrepresented categories of biological processes and molecular functions. Among the overrepresented biological processes were multiple development related processes along with the category of circadian rhythm. Using the FlyBase annotations, I identified a number of genes with circadian or transmitter-related signaling functions. The largest categories of molecular functions were ATP binding and structural components of ribosomes. In looking at the overall landscape of astrocyte protein synthesis, I observed two major phases of translation throughout the day, similar to a previous gene profiling study on clock cells. Together, these studies add to our knowledge of glial functions in regulating circadian behavior. Insights into how glial cells interact with neurons to modulate behavior advance our understanding of pathologies that may result from glial dysfunction.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Neuroscience.; Advisor: Rob Jackson.; Committee: Michele Jacob, Leon Reijmers, Chris Dulla, and David Van Vactor.; Keyword: Neurosciences.